2019
DOI: 10.1021/acs.est.8b06628
|View full text |Cite
|
Sign up to set email alerts
|

Versatile Surface Modification of TFC Membrane by Layer-by-Layer Assembly of Phytic Acid–Metal Complexes for Comprehensively Enhanced FO Performance

Abstract: Polyamide TFC membranes are widely applied in membrane-based water treatment but generally suffer various fouling problems. In this work, the layer-by-layer assembly of phytic acid (PA) and metal ions (M) is constructed on the surface TFC membrane for the first time, to improve the bio/organic fouling resistances and separation performance of TFC membranes simultaneously. The PA molecule with six phosphonic acid groups of strong chelation ability acts as the organic ligand, and the metal ion acts as the inorga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 74 publications
(44 citation statements)
references
References 46 publications
2
42
0
Order By: Relevance
“…The peak appearing at 717.7 eV belongs to the satellite peak of the Fe element [ 38 ]. From the spectrum of P 2p ( Figure 2 e), the presence of P = O (132.8 eV), P-OH (133.4 eV), and P-O-Fe (134.2 eV) are presented, confirming that PhA was successfully grafted onto the membrane through the Fe 3+ complexation [ 30 ].…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…The peak appearing at 717.7 eV belongs to the satellite peak of the Fe element [ 38 ]. From the spectrum of P 2p ( Figure 2 e), the presence of P = O (132.8 eV), P-OH (133.4 eV), and P-O-Fe (134.2 eV) are presented, confirming that PhA was successfully grafted onto the membrane through the Fe 3+ complexation [ 30 ].…”
Section: Resultsmentioning
confidence: 93%
“…Compared with the weak acidic phenolic hydroxyl groups, strong phosphonic acids have a higher degree of ionization, showing more affinity toward water molecules. As one of the non-toxic and natural phosphonic acids, phytic acids (PhA) have attracted extensive attention for enhancing the anti-fouling properties of membranes [ 30 , 31 ]. A phytic acid molecule contains six electronegative phosphate groups which can chelate a variety of metal ions; the PhA-metal complex system provides a new strategy for surface modification of membranes [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To compare the antibacterial behaviors of the Cu NPs and Ag NPs, as illustrated in Figure 5, Ag + and Cu 2+ were used to modify the TFC membranes (TFC_PA-Ag and TFC_PA-Cu). [97] The results of the inhibition zone test showed that the inhibitory effects of the TFC_PA-Ag membrane against E. coli were significantly larger than those of the TFC_PA-Cu membrane. Moreover, the number of E. coli was significantly higher for TFC_PA-Cu, despite better hydrophilicity.…”
Section: Metal Nanoparticlesmentioning
confidence: 96%
“…Antibiofouling properties of TFC, TFC_PA-Ag, and TFC_PA-Cu membranes: a) the inhibition zone test against E. coli and b) SEM images of different TFC membranes after exposure to E. coli suspension. Reproduced with permission [97]. Copyright 2019, American Chemical Society.…”
mentioning
confidence: 99%